Negative pole piece and lithium ion battery
By designing and controlling the proportion of active material particles of different particle sizes in the negative electrode sheet, increasing the porosity of the second electrode material layer, the poor cycle life problem caused by the design of thick electrodes in lithium-ion batteries is solved, and high energy density, excellent cycle performance and fast charging performance are achieved.
Patent Information
- Application Number
- CN202411277212.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-21
AI Technical Summary
When using thick electrode designs, the increase in electrode thickness leads to the extended transmission path of electrons and ions, which in turn increases the polarization of the battery, deteriorates the dynamics, and shows defects such as poor cycle life.
By designing the first electrode material layer and the second electrode material layer of the current collector in the negative electrode sheet, the ratio of the first active material particles and the second active material particles of different particle sizes is adjusted, so that there are more large particles in the second electrode material layer to increase the porosity and improve the wetting effect of the electrolyte.
Effectively exert the function of the first electrode material layer, improve the electrode reaction kinetics, improve the cycling and electrical performance of the battery cell, and at the same time strengthen the electrode immersion of the electrolyte, improve the cycling and fast charging performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a lithium-ion battery. Background Art
[0002] With the increasing popularity of new energy electric vehicles, consumers are paying more and more attention to the driving range and charging time. To achieve high energy density lithium-ion batteries, it is necessary to use a combination of positive and negative electrodes with higher specific capacity (such as high nickel positive electrode and silicon carbon negative electrode) and thick electrode design. The development and use of thick electrodes can effectively increase the proportion of active materials in the battery, thereby increasing the battery energy density and reducing costs.
[0003] However, the use of thick electrodes also faces a series of problems. The increase in electrode thickness will prolong the transmission path of electrons and ions, increase battery polarization, and deteriorate electrode kinetics, which will lead to defects such as poor cycle life in the battery. Summary of the invention
[0004] The embodiments of the present invention provide a negative electrode plate and a lithium-ion battery, which can improve the technical problem of poor cycle performance of existing batteries.
[0005] In the first aspect, an embodiment of the present invention provides a negative electrode plate, comprising a current collector and a first electrode material layer and a second electrode material layer stacked in sequence on the current collector in a direction away from the current collector, wherein the first electrode material layer and the second electrode material layer both comprise active materials, the active materials comprise first active material particles and second active material particles, the particle size of the first active material particles is greater than the particle size of the second active material particles, the total mass of the first active material particles in the first electrode material layer is less than the total mass of the second active material particles, and the total mass of the first active material particles in the second electrode material layer is greater than the total mass of the second active material particles.
[0006] In one embodiment, based on the total mass of the active material particles in the second electrode material layer, the mass percentage of the first active material is 55%-95%, and the mass percentage of the second active material particles is 5%-45%; and / or,
[0007] Based on the total mass of the active material particles in the first electrode material layer, the mass percentage of the first active material particles is 5%-45%, and the mass percentage of the second active material particles is 55%-95%; and / or,
[0008] The D50 of the first active material particles is 12-20 μm; and / or,
[0009] The D50 of the second active material particles is 5-12 μm; and / or,
[0010] The gram capacity of the active material is 400-2000 mAh / g.
[0011] In one embodiment, the active material includes one or more of carbon materials, silicon materials and lithium-gold materials.
[0012] In one embodiment, the carbon material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, and activated carbon.
[0013] In one embodiment, the silicon material includes one or more of silicon, silicon carbon and silicon oxygen; the lithium gold material includes one or more of lithium alloy, lithium aluminum alloy and lithium titanium alloy.
[0014] In one embodiment, a mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is (3-8):(2-9).
[0015] In one embodiment, the mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is 1:1; and / or,
[0016] The mass ratio of the second active material particles to the first active material particles in the first electrode material layer is the same as the mass ratio of the first active material particles to the second active material particles in the second electrode material layer.
[0017] In one embodiment, the first electrode material layer and the second electrode material layer both further include a conductive agent, and the mass ratio of the conductive agent in the first electrode material layer to the conductive agent in the second electrode material layer is (2-9):(1-8).
[0018] In one embodiment, the first electrode material layer and the second electrode material layer also include a binder. Based on the total mass of the binder in the first electrode material layer and the second electrode material layer, the mass percentage of the binder in the first electrode material layer is 55-95, and the mass percentage of the binder in the second electrode material layer is 5-45.
[0019] In one embodiment, the ratio of the sum of the mass of the active material in the first electrode material layer and the second electrode material layer, the sum of the mass of the conductive agent, and the sum of the mass of the binder is (71-115):(1-10):(1.5-30).
[0020] In one embodiment, the conductive agent includes one or more of acetylene black, conductive carbon black, graphene and carbon nanotubes; and / or,
[0021] The binder includes one or more of polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, sodium alginate, carboxymethyl chitosan and polyacrylonitrile.
[0022] In one embodiment, the active material includes graphite and silicon, the binder includes polyacrylic acid, styrene-butadiene rubber and sodium carboxymethyl cellulose, and the mass ratio of the graphite, the silicon, the polyacrylic acid, the styrene-butadiene rubber and the sodium carboxymethyl cellulose is (70-95):(1-20):(0.5-10):(0.5-10):(0.5-10).
[0023] In a second aspect, an embodiment of the present invention provides a lithium-ion battery, comprising the above-mentioned negative electrode plate.
[0024] In an embodiment of the present invention, by regulating the ratio of the first active material particles and the second active material particles of different particle sizes in the first electrode material layer and the second electrode material layer, the second electrode material layer has more large particles, so as to increase the porosity of the second electrode material layer and enhance the infiltration effect of the electrolyte, so that the function of the first electrode material layer can be effectively exerted, which is beneficial to the transmission of lithium ions and electrons in the electrode pores, improves the electrode reaction kinetics, and improves the cycle performance and electrical performance of the battery cell; at the same time, the infiltration of the electrolyte into the electrode can be enhanced, which is beneficial to the charge exchange at the interface between the electrode and the electrolyte, so that excellent cycle performance and fast charging performance can be exhibited in high energy density lithium-ion batteries. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] The technical solution of this application is as follows:
[0027] In a first aspect, an embodiment of the present application provides a negative electrode plate, comprising a current collector and a first electrode material layer and a second electrode material layer stacked in sequence on the current collector in a direction away from the current collector, wherein the first electrode material layer and the second electrode material layer both comprise active materials, the active materials comprise first active material particles and second active material particles, the particle size of the first active material particles is greater than the particle size of the second active material particles, the total mass of the first active material particles in the first electrode material layer is less than the total mass of the second active material particles, and the total mass of the first active material particles in the second electrode material layer is greater than the total mass of the second active material particles.
[0028] In the present application, by regulating the ratio of the first active material particles and the second active material particles of different particle sizes in the first electrode material layer and the second electrode material layer, the second electrode material layer has more large particles, so as to increase the porosity of the second electrode material layer and improve the infiltration effect of the electrolyte, so that the function of the first electrode material layer can be effectively exerted, which is beneficial to the transmission of lithium ions and electrons in the electrode pores, can improve the electrode reaction kinetics, and improve the cycle performance and electrical performance of the battery cell; at the same time, the infiltration of the electrolyte into the electrode can be enhanced, which is beneficial to the charge exchange at the interface between the electrode and the electrolyte, so that excellent cycle performance and fast charging performance can be exhibited in high energy density lithium ion batteries. In the present application, the active materials in the first electrode material layer and the second electrode material layer can be the same material or different materials, and the first active material particles and the second active material particles can be the same material or different materials.
[0029] In some embodiments, based on the total mass of the active material in the second electrode material layer, the mass percentage of the first active material particles is 55%-95%, for example, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc., and the mass percentage of the second active material particles is 5%-45%, for example, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, etc. Within this range, the porosity of the upper electrode material layer can be effectively increased, so that the function of the lower electrode material layer can be effectively exerted.
[0030] In some embodiments, based on the total mass of the active material particles in the first electrode material layer, the mass percentage of the first active material particles is 5%-45%, for example, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, etc., and the mass percentage of the second active material particles is 55%-95%, for example, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc. Within this range, the function of the lower electrode material layer can be effectively exerted, which is beneficial to the transmission of lithium ions and electrons in the electrode pores, can enhance the infiltration of the electrolyte into the electrode, and is beneficial to the charge exchange at the interface between the electrode and the electrolyte.
[0031] In some embodiments, the D50 of the first active material particles is 12-20 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc. Within this range, the porosity of the upper and lower electrode materials can be controlled, thereby effectively exerting the functions of the upper and lower electrode material layers.
[0032] In some embodiments, the D50 of the second active material particles is 5-12 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, etc. Within this range, the porosity of the upper and lower electrode materials can be controlled, thereby effectively exerting the functions of the upper and lower electrode material layers.
[0033] In one embodiment, the mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is (3-8): (2-9), for example, 3:2, 3:5, 3:7, 3:9, 5:2, 5:5, 5:7, 5:9, 8:2, 8:5, 8:7, 8:9, etc. Within this range, the porosity of the upper and lower electrode materials can be controlled, so as to effectively play the functions of the upper and lower electrode material layers, facilitate the transmission of lithium ions and electrons in the electrode pores, enhance the infiltration of the electrolyte into the electrode, and facilitate the charge exchange at the interface between the electrode and the electrolyte.
[0034] In some embodiments, the mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is 1:1.
[0035] In some embodiments, the mass ratio of the second active material particles to the first active material particles in the first electrode material layer is the same as the mass ratio of the first active material particles to the second active material particles in the second electrode material layer.
[0036] In some embodiments, both the first electrode material layer and the second electrode material layer also include a conductive agent, and the mass ratio of the conductive agent in the first electrode material layer to the conductive agent in the second electrode material layer is (2-9):(1-8), for example, it can be 2:8, 3:4, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, etc.
[0037] In the present application, by controlling the mass ratio of the conductive agent in the first electrode material layer and the second electrode material layer, the conductive network in the first electrode material layer and the second electrode material layer can be improved, thereby improving the electrode reaction kinetics. In the present application, the conductive agent in the first electrode material layer and the second electrode material layer can be the same material or different materials.
[0038] In some embodiments, the first electrode material layer and the second electrode material layer both further include a binder. Based on the total mass of the binder in the first electrode material layer and the second electrode material layer, the mass percentage of the binder in the first electrode material layer is 55%-95%, for example, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc., and the mass percentage of the binder in the second electrode material layer is 5%-45%, for example, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, etc. In the present application, the binders in the first electrode material layer and the second electrode material layer may be the same material or different materials.
[0039] In the present application, by controlling the mass ratio of the binder in the first electrode material layer and the second electrode material layer, the amount of binder in the upper layer is reduced, the liquid phase resistance can be reduced, the porosity of the upper layer can be increased, and the transmission of lithium ions and electrons in the electrode pores can be facilitated. At the same time, the wetting of the electrolyte into the electrode can be enhanced, which is beneficial to the charge exchange at the interface between the electrode and the electrolyte, thereby exhibiting excellent cycle performance and fast charging performance in high energy density lithium-ion batteries; in addition, the binder will float up during the baking process of the electrode sheet, and the more binder in the lower layer can enhance the bonding force between the electrode material and the current collector.
[0040] In some embodiments, the ratio of the mass sum of the active materials in the first electrode material layer and the second electrode material layer, the mass sum of the conductive agent, and the mass sum of the binder is (71-115):(1-10):(1.5-30), for example, it can be 71:1:1.5, 75:2:6, 80:3:9, 85:4:12, 90:5:15, 95:6:18, 100:7:21, 105:8:24, 110:9:27, 115:10:30.
[0041] In some embodiments, the active material includes one or more of graphite, silicon material, and lithium alloy material.
[0042] In some embodiments, the gram capacity of the active material is 400-2000mAh / g, for example, 400mAh / g, 600mAh / g, 800mAh / g, 1000mAh / g, 1200mAh / g, 1400mAh / g, 1600mAh / g, 1800mAh / g, 2000mAh / g, etc.
[0043] In the present application, the active material may be a mixture of several materials, and the gram capacity of the active material is the average gram capacity of the several materials.
[0044] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, and activated carbon.
[0045] In some embodiments, the silicon material includes one or more of silicon, silicon carbon, and silicon oxygen.
[0046] In some embodiments, the lithium alloy material includes one or more of a lithium alloy, a lithium aluminum alloy, and a lithium titanium alloy.
[0047] In some embodiments, the conductive agent includes one or more of acetylene black, conductive carbon black, graphene, and carbon nanotubes.
[0048] In some embodiments, the carbon nanotubes include multi-walled carbon nanotubes and / or single-walled carbon nanotubes.
[0049] In some embodiments, the binder includes one or more of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), sodium alginate, carboxymethyl chitosan and polyacrylonitrile.
[0050] In some embodiments, the active material includes graphite and silicon, and the binder includes polyacrylic acid, styrene-butadiene rubber and sodium carboxymethyl cellulose. The mass ratio of graphite, silicon, polyacrylic acid, styrene-butadiene rubber and sodium carboxymethyl cellulose is (70-95):(1-20):(0.5-10):(0.5-10):(0.5-10), for example, it can be 70:4:0.5:0.5:0.5, 75:7:2:2:2, 80:10:4:4:4, 85:13:5.5:5.5:5.5, 90:17:7.5:7.5:7.5, 95:20:10:10:10, etc.
[0051] In a second aspect, an embodiment of the present application provides a lithium-ion battery, comprising the above-mentioned negative electrode plate.
[0052] The following is a description with reference to specific embodiments.
[0053] Example 1
[0054] Sodium carboxymethyl cellulose (CMC) powder and deionized water were mixed at a mass ratio of 0.57:23.40 and stirred evenly to obtain CMC glue;
[0055] Weigh 45.72 kg of graphite (D50 is 20 μm, gram capacity is 350 mAh / g) and 4.46 kg of fumed silicon material SiC (D50 is 10 μm, gram capacity is 1800 mAh / g), dry mix them, add 23.97 kg of stirred CMC glue, pre-mix them, then mix and stir 8.84 kg of polyacrylic acid (PAA) binder, 0.28 kg of conductive carbon black, and 4.19 kg of carbon nanotubes, add water to adjust the viscosity, and finally add 0.62 kg of styrene-butadiene rubber (SBR) binder to obtain an upper slurry, and control the discharge viscosity to be maintained at 5000 mPa.s;
[0056] Weigh 45.72 kg of graphite (D50 is 10 μm, gram capacity is 350 mAh / g) and 4.46 kg of fumed silicon material SiC (D50 is 20 μm, gram capacity is 1800 mAh / g), dry mix them, add 23.97 kg of stirred CMC glue, pre-mix them, then mix and stir 8.84 kg of polyacrylic acid (PAA) binder, 0.28 kg of conductive carbon black, and 4.19 kg of carbon nanotubes, add water to adjust the viscosity, and finally add 0.62 kg of styrene-butadiene rubber (SBR) binder to obtain the lower slurry, and control the discharge viscosity to be maintained at 5000 mPa.s;
[0057] The prepared lower slurry and upper slurry were sequentially coated on the current collector using a double-layer coating die at a coating speed of 15 m / min, and then baked at 100° C. to obtain a negative electrode sheet.
[0058] Example 2
[0059] This embodiment is basically the same as Example 1, except that in this embodiment, the amount of graphite (D50 is 20 μm, gram capacity 350 mAh / g) in the upper slurry is 37.64 kg, and the amount of graphite (D50 is 10 μm, gram capacity 350 mAh / g) is 8.09 kg, and the amount of graphite (D50 is 10 μm, gram capacity 350 mAh / g) in the lower slurry is 37.64 kg, and the amount of graphite (D50 is 20 μm, gram capacity 350 mAh / g) is 8.09 kg.
[0060] Example 3
[0061] This embodiment is basically the same as Example 1, except that in this embodiment, the amount of graphite (D50 is 20 μm, gram capacity 350 mAh / g) in the upper slurry is 27.60 kg, and the amount of graphite (D50 is 10 μm, gram capacity 350 mAh / g) is 18.12 kg, and the amount of graphite (D50 is 10 μm, gram capacity 350 mAh / g) in the lower slurry is 27.60 kg, and the amount of graphite (D50 is 20 μm, gram capacity 350 mAh / g) is 18.12 kg.
[0062] Example 4
[0063] This embodiment is basically the same as Embodiment 1, except that the D50 of the gas phase silicon material SiC in the upper slurry in this embodiment is 5 μm.
[0064] Example 5
[0065] This embodiment is substantially the same as Embodiment 1, except that the D50 of the gas phase silicon material SiC in the upper slurry in this embodiment is 12 μm.
[0066] Example 6
[0067] This embodiment is substantially the same as Embodiment 1, except that the D50 of the graphite in the upper slurry in this embodiment is 12 μm.
[0068] Example 7
[0069] This embodiment is substantially the same as Embodiment 1, except that the D50 of the graphite in the upper slurry in this embodiment is 16 μm.
[0070] Example 8
[0071] This embodiment is basically the same as Example 1, except that in this embodiment, the amount of CMC glue in the lower layer slurry is 33.56 kg, the amount of polyacrylic acid (PAA) binder is 12.38 kg, and the amount of styrene-butadiene rubber (SBR) binder is 0.87 kg, and the amount of CMC glue in the upper layer slurry is 14.38 kg, the amount of polyacrylic acid (PAA) binder is 5.3 kg, and the amount of styrene-butadiene rubber (SBR) binder is 0.37 kg.
[0072] Example 9
[0073] This embodiment is basically the same as Example 1, except that in this embodiment, the amount of CMC glue in the lower layer slurry is 41.55 kg, the amount of polyacrylic acid (PAA) binder is 14.14 kg, and the amount of styrene-butadiene rubber (SBR) binder is 0.99 kg, and the amount of CMC glue in the upper layer slurry is 10.39 kg, the amount of polyacrylic acid (PAA) binder is 3.54 kg, and the amount of styrene-butadiene rubber (SBR) binder is 0.25 kg.
[0074] Example 10
[0075] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the amount of conductive carbon black in the lower slurry is 0.39 kg, and the amount of carbon nanotubes is 5.87 kg, and the amount of conductive carbon black in the upper slurry is 0.17 kg, and the amount of carbon nanotubes is 2.51 kg.
[0076] Embodiment 11
[0077] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the amount of conductive carbon black in the lower layer slurry is 0.45 kg, and the amount of carbon nanotubes is 6.70 kg, and the amount of conductive carbon black in the upper layer slurry is 0.11 kg, and the amount of carbon nanotubes is 1.68 kg.
[0078] Comparative Example 1
[0079] This comparative example is basically the same as Example 1, with the only difference being that the amounts of graphite (D50 is 10 μm, gram capacity is 350 mAh / g) and gas phase silicon material SiC (D50 is 20 μm, gram capacity is 1800 mAh / g) used in the upper slurry and the lower slurry in this comparative example are both 22.865 kg.
[0080] Comparative Example 2
[0081] This comparative example is basically the same as Example 1, with the only difference that in this comparative example, the amount of graphite (D50 is 10 μm, gram capacity 350 mAh / g) in the upper slurry is 45.72 kg, and the amount of gas-phase silicon material SiC (D50 is 20 μm, gram capacity 1800 mAh / g) is 4.46 kg, and the amount of graphite (D50 is 20 μm, gram capacity 350 mAh / g) in the lower slurry is 45.72 kg, and the amount of gas-phase silicon material SiC (D50 is 10 μm, gram capacity 1800 mAh / g) is 4.46 kg.
[0082] Test example:
[0083] The obtained negative electrode sheet is combined with the ternary positive electrode (LiNi 0.9 Co 0.05 Mn 0.05O2) were combined to form a full battery, and the cycle life and fast charging performance were tested. The test results are shown in Table 1.
[0084] Cycle life test: At 25℃, 1C constant current and constant voltage charging to 4.2V, 0.05C current cutoff; 1C constant current discharge to 2.5V, cycle test.
[0085] Fast charging test: Use 12min fast charging to simulate the working conditions, charge from 10% SOC to 80% SOC, then use 0.5C constant current and constant voltage to charge to 4.2V, 1C constant current discharge to 2.5V, and cycle test.
[0086] Table 1
[0087]
[0088] From Table 1, we can see that:
[0089] Compared with Example 1, Example 2 and Example 3, the battery capacity retention rate in Example 3 is higher. It can be seen that the ratio of large particles to small particles of the active material in the second electrode material layer and the first electrode material will affect the battery capacity retention rate.
[0090] Compared with Example 1, Example 6 and Example 7, the battery capacity retention rate in Example 7 is higher. It can be seen that the large particle size of the active material in the second electrode material will affect the battery capacity retention rate.
[0091] Compared with Example 1, Example 8 and Example 9, the battery capacity retention rate of Example 8 and Example 9 is higher. It can be seen that the battery capacity retention rate can be improved by making the binder of the first electrode material layer more massive than the binder of the second electrode material layer.
[0092] Compared with Example 1, Example 10 and Example 11, the battery capacity retention rate of Example 10 and Example 11 is higher. It can be seen that the battery capacity retention rate can be improved by controlling the mass ratio of the conductive agent in the first electrode material layer to the conductive agent in the second electrode material layer.
[0093] Compared with Comparative Examples 1 and 2, the battery capacity retention rate of the embodiment is higher. It can be seen that the battery capacity retention rate can be improved by making the mass of large particles of active material in the second electrode material layer greater than the mass of small particles of active material and making the mass of large particles of active material in the first electrode material smaller than the mass of small particles of active material.
[0094] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A negative electrode plate, characterized in that: It includes a current collector and a first electrode material layer and a second electrode material layer stacked in sequence on the current collector in a direction away from the current collector, the first electrode material layer and the second electrode material layer both include active materials, the active materials include first active material particles and second active material particles, the particle size of the first active material particles is larger than the particle size of the second active material particles, the total mass of the first active material particles in the first electrode material layer is smaller than the total mass of the second active material particles, and the total mass of the first active material particles in the second electrode material layer is larger than the total mass of the second active material particles.
2. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the active material in the second electrode material layer, the mass percentage of the first active material particles is 55%-95%, and the mass percentage of the second active material particles is 5%-45%; and / or, Based on the total mass of the active material particles in the first electrode material layer, the mass percentage of the first active material particles is 5%-45%, and the mass percentage of the second active material particles is 55%-95%; and / or, The D50 of the first active material particles is 12-20 μm; and / or, The D50 of the second active material particles is 5-12 μm; and / or, The gram capacity of the active material is 400-2000 mAh / g.
3. The negative electrode sheet according to claim 1, characterized in that: The active material includes one or more of carbon materials, silicon materials and lithium alloy materials.
4. The negative electrode sheet according to claim 3, characterized in that: The carbon material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, and activated carbon; and / or, The silicon material includes one or more of silicon, silicon carbon and silicon oxygen; and / or, The lithium alloy material includes one or more of lithium alloy, lithium aluminum alloy and lithium titanium alloy.
5. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is (3-8):(2-9).
6. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the active material in the first electrode material layer to the active material in the second electrode material layer is 1:1; and / or, The mass ratio of the second active material particles to the first active material particles in the first electrode material layer is the same as the mass ratio of the first active material particles to the second active material particles in the second electrode material layer.
7. The negative electrode sheet according to claim 1, characterized in that: The first electrode material layer and the second electrode material layer both further include a conductive agent, and the mass ratio of the conductive agent in the first electrode material layer to the conductive agent in the second electrode material layer is (2-9):(1-8).
8. The negative electrode sheet according to claim 7, characterized in that: The first electrode material layer and the second electrode material layer also include a binder. Based on the total mass of the binder in the first electrode material layer and the second electrode material layer, the mass percentage of the binder in the first electrode material layer is 55-95, and the mass percentage of the binder in the second electrode material layer is 5-45.
9. The negative electrode sheet according to claim 8, characterized in that: The ratio of the sum of the mass of the active material in the first electrode material layer and the second electrode material layer, the sum of the mass of the conductive agent, and the sum of the mass of the binder is (71-115):(1-10):(1.5-30).
10. The negative electrode sheet according to claim 8, characterized in that: The conductive agent includes one or more of acetylene black, conductive carbon black, graphene and carbon nanotubes; and / or, The binder includes one or more of polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, sodium alginate, carboxymethyl chitosan and polyacrylonitrile.
11. The negative electrode sheet according to claim 8, characterized in that: The active material includes graphite and silicon, the binder includes polyacrylic acid, styrene-butadiene rubber and sodium carboxymethyl cellulose, and the mass ratio of the graphite, the silicon, the polyacrylic acid, the styrene-butadiene rubber and the sodium carboxymethyl cellulose is (70-95): (1-20): (0.5-10): (0.5-10): (0.5-10).
12. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 1 to 11.
Citation Information
Patent Citations
Negative pole piece, electrochemical device and electronic device
CN111261834A
Positive plate and lithium ion battery
CN113793930A
Negative plate of lithium ion battery
CN116053412A
Silicon-based negative pole piece, preparation method thereof and lithium ion battery
CN116387448A
Negative Electrode for Secondary Battery, and Secondary Battery Including Same
US20220140342A1
Cited By
Negative electrode sheet and lithium-ion battery
WO2026056366A1